2017
DOI: 10.1001/jamadermatol.2016.4670
|View full text |Cite
|
Sign up to set email alerts
|

Association of Quality of Life and Location of Lesions in Patients With Vitiligo

Abstract: Vitiligo is a chronic depigmenting disorder of multifactorial etiology affecting 0.5% to 1% of the population. The white macules characteristic of vitiligo have been shown to have a profound impact on quality of life (QOL) in affected individuals. 1,2 The goal of this cross-sectional study was to determine the location(s) of vitiligo lesions that has the greatest effect on QOL.Methods | All patients enrolled in the Dallas Vitiligo Registry (DVR) at the University of Texas Southwestern (UTSW) Medical Center f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
0
17
1
1
Order By: Relevance
“…In contrast, the Vitiligo-specific QoL (VitiQoL) instrument has only been reported in eight studies [ 13 , 16 , 29 , 32 , 67 , 80 , 88 , 115 ] using our search parameters; half were published in the past year, of which two were clinical trials. There were no notable regional differences in VitiQoL scores among studies, which were conducted in each of the seven geographic regions, with two in North America.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the Vitiligo-specific QoL (VitiQoL) instrument has only been reported in eight studies [ 13 , 16 , 29 , 32 , 67 , 80 , 88 , 115 ] using our search parameters; half were published in the past year, of which two were clinical trials. There were no notable regional differences in VitiQoL scores among studies, which were conducted in each of the seven geographic regions, with two in North America.…”
Section: Resultsmentioning
confidence: 99%
“…Factors that were significantly associated with higher psychosocial (Fig. 3 ) or overall QoL burden were female sex (30 studies) [ 15 , 21 , 25 , 28 , 30 , 45 , 46 , 49 , 51 , 57 , 62 , 66 68 , 70 , 88 , 90 , 99 , 104 , 107 , 109 , 112 , 113 , 120 , 123 , 132 , 143 , 146 , 154 , 158 ], lesion location in visible areas (e.g., face, hands [17 studies]) [ 4 , 25 , 35 , 37 , 49 , 62 , 70 , 80 , 89 , 90 , 92 , 101 , 122 , 123 , 138 , 143 , 151 ] or genitals (eight studies) [ 70 , 89 , 97 , 105 , 115 , 122 , 144 , 151 ], younger age (16 studies; particularly those aged <30 years and more so in adolescents) [ 17 , 25 , 30 , 48 , 49 , 62 , 67 , 68 , 70 ,…”
Section: Resultsmentioning
confidence: 99%
“…Another study found that lesions on the genital area were associated with a high burden 11 . Florez‐Pollack et al illustrated that lesions on the hands were even more bothersome compared with the face and neck 15 . We hypothesize that the disease burden and its relation to the location of the various vitiligo lesions could be correlated with the demand for new therapies.…”
Section: Introductionmentioning
confidence: 78%
“…Vitiligo is a common autoimmune depigmentation disorder affecting 0.5%–2% of the population, and it remains a major challenge in dermatology (Alikhan, Felsten, Daly, & Petronic‐Rosic, ). Vitiligo has a substantial negative impact on quality of life in affected patients, especially those with the involvement of the face (Bae et al., ; Florez‐Pollack et al., ). Although the face is known to be the most responsive body part to conventional phototherapy (Nicolaidou, Antoniou, Stratigos, Stefanaki, & Katsambas, ), the treatment of facial vitiligo is not always successful.…”
Section: Introductionmentioning
confidence: 99%